Answer:
![\bold{-(1)/(2√(4-x))}](https://img.qammunity.org/2023/formulas/mathematics/college/5zfjgfkipcyea0wifyowbgyzl11z4p44m3.png)
Explanation:
This can also be solved without using limits
Let
![y = √(4-x)](https://img.qammunity.org/2023/formulas/mathematics/college/tnu7ayw2ooon6sv7hby6rq7nwspt2ct02l.png)
The power rule of derivatives says that if we have a function
![y = a.x^n,](https://img.qammunity.org/2023/formulas/mathematics/college/v2h69i1i51twr4um1etkth41yo4cg1v0rb.png)
then the first derivative given by
or abbreviated as
is given by
![n(ax^(n-1))](https://img.qammunity.org/2023/formulas/mathematics/college/40eo8648pgk2saxsw1xtlnis4efxu8duti.png)
We can use this in combination with the substitution rule of calculus
Let u = 4-x
Then we have
![(du)/(dx) = (d(4))/(dx) - (d(x))/(dx) = 0 -1 = -1](https://img.qammunity.org/2023/formulas/mathematics/college/xfmoshpk30vn7z7xefyghbdilbuvlh17tl.png)
(First differential of a constant is 0 and first differential of x is 1)
Substituting for u in the original expression
we get
![(dy)/(du) = (d)/(du) (√(u)) = (d)/(du)(u^(1/2)) = (1)/(2) u^{(1)/(2) -1} = (1)/(2) u^(-1/2) =(1)/(2) (1)/(√(u) )](https://img.qammunity.org/2023/formulas/mathematics/college/sa7lhnblpwhg61pk4vqmpafd924sttpy99.png)
The substitution rule states
![(dy)/(dx) = (dy)/(du) (du)/(dx)](https://img.qammunity.org/2023/formulas/mathematics/college/gbbtlcgxxpiaeafwjwr8jk6cpcv11ffaay.png)
So
![(dy)/(dx) = (1)/(2√(u) ) . (-1)](https://img.qammunity.org/2023/formulas/mathematics/college/odck49yuqba1i9irupts2afkzwxifu2bzv.png)
Substituting for u in terms of x we get
![(dy)/(dx) = (1)/(2√(4-x) ) . (-1) = -(1)/(2√(4-x))](https://img.qammunity.org/2023/formulas/mathematics/college/wlnviaik5g022qxibifgse9vtqfdi7bsqf.png)